INFERIORITY FEELING OF JACK DAWSON IN JAMES CAMERON’S TITANIC: AN INDIVIDUAL PSYCHOLOGICAL APPROACH - WULANDARI, DANI INDAH (2010)
The object of this research is the movie entitled Titanic by James Cameron. The amazing movie Titanic is best work of 1990s. James Cameron gets more appraisals about his work, Titanic. The major problem of this study is how inferiority feeling of Jack Dawson is reflected in the movie James Cameron’s Titanic based on Individual Psychological Approach. So, this research paper answers the major problem within the suggestions. The researcher employs qualitative research method. In this method, the researcher uses two data resources namely primary and secondary data sources. The primary data source is the movie James Cameron’s Titanic itself. The secondary data source is the books about individual psychology and the other source related to the analysis. The method of data collection is descriptive technique. The results of this study are two points. First, it is structural elements of the movie which presents unity. It appears in the exposition, complication, climax, and resolution of the story. The story is preceded with introduction of each character. Then, it raises problem among the major character, Jack Dawson and others. The problem comes to huge trouble. He is fighting for his love. It turns into resolution when Jack knows that his love is worthy for his girl, Rose DeWitt Bukater. Second, it is the individual psychological analysis that shows the striving of a poor artist to gain his true love and he successfully over comes his inferiority feeling.